Análisis del desempeño técnico, económico y ambiental de motocarros de combustión interna bajo condiciones reales de operación con respecto a vehículos convencionales para distribución de mercancías en la última milla para tres ciudades de Colombia. (2022)
The transportation industry in the last mile goods distribution stage is in a constant search for solutions to optimize this process and be able to meet customer demand, not only delivering their products in less time, but also at a lower operating cost, and in turn generating an increase in the profit margin for the company. The vehicles currently used for the distribution of goods in the last mile are of large size, which makes it difficult to comply with the previously established times, since they have difficulties to access areas where the roads are reduced, have a high fuel consumption and generate a high level of pollutant emissions.